Individual versus group peer feedback: an empirical study on perceived usefulness in a higher education course on evaluation - Truffelli, Elisa; Rosa, Alessandra (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
In the field of Assessment for Learning (AfL) in higher education, it is widely recognised that peer feedback plays a strategic role in fostering learning. While numerous studies have demonstrated the positive impact of peer-review and peer feedback on student performance, the literature would benefit from an in-depth analysis of the conditions that facilitate this synergistic interaction. Few studies to date have considered the implications of individual versus group-led peer feedback practice (Cho & MacArthur, 2010). This case study was conducted in the context of a master’s degree course on evaluation. The innovative process undertaken centred upon an authentic task of formative evaluation among peers and the production of anonymous reviews and feedback, both individual and group-based. Participation was voluntary. The focus was upon the perceived usefulness among students of the different approaches to peer feedback. The results show broad recognition of the benefits inherent in the production of feedback among peers, albeit for some merely the opportunity for comparison with peers’ work, for others however, a deeper understanding of assessment criteria and submissions. In general, group feedback from peers was considered more informative, less normative and more valuable than individual feedback (beyond the purpose of assignment enhancement).